Social Anxiety and Quality of Life among Female Adolescents with Premenstrual Syndrome: A Cross-Sectional Study - Misbah Arshad; Quratulaine Asim; Eshwa Butt; Sarah Mufti (Research Journal of Psychology, 2025)
This cross-sectional correlational study investigated the relationship between premenstrual syndrome (PMS), social anxiety, and quality of life (QOL) among adolescent females age ranging 13 to 16 from three districts in Punjab, Pakistan Gujrat, Jhelum, and Mandi Bahauddin. A total of 566 school and madrasah-going girls were selected through convenience sampling. Validated tools including the WHOQOL-BREF, Social Anxiety Scale for Adolescents, and the Premenstrual Syndrome Scale were used to assess respective variables. Data analysis via SPSS (Version 21) using non-parametric tests revealed significant variations across demographic and institutional lines. PMS symptoms were more prevalent among urban and madrasah students, while social anxiety was higher in rural and school-going girls. Furthermore, QOL was comparatively lower in urban and school populations. The findings highlighted that PMS significantly contributes to elevated social anxiety and reduced QOL, emphasizing the need for early awareness, mental health support, and targeted interventions for adolescent girls in diverse educational settings.